Estimación del daño causado por acridios en pasturas naturales. I : Reducción de forraje debida a Dichroplus pratensis Bruner - Sánchez, Norma Elba (1983)
A quantitative evaluation of forage losses caused by the grasshopper Dichroplus pratensis Bruner was carried out in a natural pasture of La Pampa province. (Argentina). The tests were done in the field, and the amount of forage consumed plus forage wasted was determined. The average reduction was 150,26 mg. during 4th. instar, 340,688 mg. during 5th. instar and 1.826,603 mg. for the adult stage during the sexual maduration period, and 201,419 mg. for the adult stage during post maduration period. An estimated loss of 25,20 Kg/Ha will result from a density of 1 specimen/m2 during the 4th. instar and through the adult stage. The population living during 1981-82 in the place of study caused a reduction of forage of 303,19 kg/Ha. from the 4th instar through adult stage.